2021
DOI: 10.5194/hess-25-237-2021
|View full text |Cite
|
Sign up to set email alerts
|

Hillslope and groundwater contributions to streamflow in a Rocky Mountain watershed underlain by glacial till and fractured sedimentary bedrock

Abstract: Abstract. Permeable sedimentary bedrock overlain by glacial till leads to large storage capacities and complex subsurface flow pathways in the Canadian Rocky Mountain region. While some inferences on the storage and release of water can be drawn from conceptualizations of runoff generation (e.g., runoff thresholds and hydrologic connectivity) in physically similar watersheds, relatively little research has been conducted in snow-dominated watersheds with multilayered permeable substrates that are characteristi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…The groundwater contribution from the soil upper zone was high in the summer months because of high percolation to the aquifer as a result of the rise in rainfall-runoff and glaciers melting. The other studies conducted by Orlova and Branfireun (2014) and Spencer et al (2021) have also confirmed that the contribution of water from the soil deep zone is dominant in the dry period while the contribution of water from the soil shallow zone is dominant in the wet season. Moreover, it was observed that deep soils with large storage capacities control the baseflow during dry periods (Shanley et al, 2015;Floriancic et al, 2018).…”
Section: Discussionmentioning
confidence: 54%
“…The groundwater contribution from the soil upper zone was high in the summer months because of high percolation to the aquifer as a result of the rise in rainfall-runoff and glaciers melting. The other studies conducted by Orlova and Branfireun (2014) and Spencer et al (2021) have also confirmed that the contribution of water from the soil deep zone is dominant in the dry period while the contribution of water from the soil shallow zone is dominant in the wet season. Moreover, it was observed that deep soils with large storage capacities control the baseflow during dry periods (Shanley et al, 2015;Floriancic et al, 2018).…”
Section: Discussionmentioning
confidence: 54%
“…Crowsnest Lake receives substantial groundwater inputs from sub-lacustrine springs and Crowsnest Creek that drain the upper reaches of the watershed [39]. Discharge in the uppermost reaches of the Crowsnest River originates as outflow from Crowsnest Lake and discharge in reaches of the Crowsnest River downstream is augmented by numerous tributary inflows that also receive substantial groundwater inputs [39][40][41]. The headwater reaches of the Crowsnest River below Crowsnest Lake are oligotrophic (mean TP = 15 µgL -1 n= 169 from 2012 to 2021: U. Silins, unpublished data).…”
Section: Study Area: Hydro-climatic Settingmentioning
confidence: 99%
“…Accordingly, fractured-aquifer characterization represents a challenge, with a relatively high cost related to the application of specialized field investigation techniques and to gathering a sufficient data set for reliable hydraulic description. The general poor understanding of how groundwater flows in fractured field sites is in contrast to the relevance of fractured environments that host elementary freshwater reservoirs worldwide (Chandra et al, 2019;Wilske et al, 2020;Spencer et al, 2021). Moreover, adequate characterization of the properties of fractured field sites concerns many subsurface engineering applications, such as the planning and operation of enhanced geothermal systems (Vogler et al, 2017;Kittilä et al, 2020), the evaluation of potential sites for a nuclear waste repositories (Follin et al, 2014;Li et al, 2022), or the description of an excavationinduced damaged zone around tunnels and openings (Armand et al, 2014;de La Vaissière et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A fractured site can be inspected locally by borehole data (e.g., core mapping and geophysical image logs such as optical or acoustic televiewer). The depth and orientation of structures intercepted by boreholes characterize fracture intensity and prevalent fracture orientations (Armand et al, 2014;Chandra et al, 2019;Tan et al, 2020;Yin and Chen, 2020;Pavičić et al, 2021); furthermore, by fit-L. M. Ringel et al: Characterization of the highly fractured zone at the Grimsel Test Site ting probability distributions to the parameters, a statistical analysis can be conducted (Barthélémy et al, 2009;Massiot et al, 2017). Single-hole and cross-hole flow and tracer tests are employed to infer permeability and connectivity between different borehole intervals (Le Borgne et al, 2006;Follin et al, 2014;de La Vaissière et al, 2015;de La Bernardie et al, 2018;Brixel et al, 2020b, a;Tan et al, 2020;Li et al, 2022), the velocity distribution (Kang et al, 2015), or transport properties (Kittilä et al, 2019;Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%